2010
DOI: 10.1051/0004-6361/201014732
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newtoninvestigations of the Lambda Orionis star-forming region (XILO)

Abstract: Context. This is the first paper of a series devoted to the Lambda Orionis star-forming region, Orion's Head, from the X-ray perspective. Our final aim is to provide a comprehensive view of this complex region, which includes several distinct associations and dark clouds. Aims. We aim to uncover the population of the central, young star cluster Collinder 69, and in particular those diskless Class III objects not identified by previous surveys based on near-and mid-infrared searches, and to establish the X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 50 publications
1
49
0
Order By: Relevance
“…Spectroscopically confirmed members from Paper I that lie in one of the two XMM-Newton pointings from Barrado et al (2011) or in the central one from Franciosini & Sacco (2011). We show in different colors objects with mass below (in black) and above (in blue) 0.3 M (the completeness limit for Barrado et al 2011). For the EW(Hα) measurements we have gathered data from Sacco et al (2008), Dolan & Mathieu (1999) and this work.…”
Section: Disk With Low Hα Binaries Clearing the Inner Disks?mentioning
confidence: 85%
See 4 more Smart Citations
“…Spectroscopically confirmed members from Paper I that lie in one of the two XMM-Newton pointings from Barrado et al (2011) or in the central one from Franciosini & Sacco (2011). We show in different colors objects with mass below (in black) and above (in blue) 0.3 M (the completeness limit for Barrado et al 2011). For the EW(Hα) measurements we have gathered data from Sacco et al (2008), Dolan & Mathieu (1999) and this work.…”
Section: Disk With Low Hα Binaries Clearing the Inner Disks?mentioning
confidence: 85%
“…Finally, the X-ray data are complete down to ∼0.3 M with detections in Barrado et al (2011) for confirmed members as low as ∼0.1 M .…”
Section: Photometric and X-ray Databasementioning
confidence: 96%
See 3 more Smart Citations